Diagnóstico de aplicação da certificação LEED NC® para uma escola de ensino técnico - Costa, Ânderson Abreu da (Universidade do Vale do Rio dos Sinos, 2011)
Brazil's construction industry is facing now a good moment in history. Incentives are coming from government to develop different types of construction, such as residential and commercial buildings, infrastructure, among others. Sustainability concepts like greenhouse gases emissions reduction and renewable energy are pushing these incentives and increasing the competition among companies from the construction business sector. In order to quantify the sustainability factors considered in their projects, companies are now adopting different green building certification criteria. In Brazil, the most common ones are Aqua, Procel Edifica, Selo Azul and LEED. In this paper, LEED NC was used to evaluate a technical school project and check whether the certification would be feasible. The main projects and memorials were analyzed followed by a site inspection. According to this study, 23 points would be obtained and LEED® certification would not be possible. On the other hand, many improvements opportunities were identified and considered feasible. In this case, LEED® certification would be achieved after project modification.
Keywords: LEED®; Construções verdes; Certificação; Sustentabilidade; Green building; Certification; Sustainability